Solubility measurement, correlation and computational analysis of p-Acetamidobenzoic acid in 12 pure solvents. (August 2021) - Zhang, Jiayin; Liu, Yumin; Shang, Zeren; Wang, Kuo; Han, Jianhua; Wu, Songgu
Highlights: Solubility of p -Acetamidobenzoic acid in 12 pure solvents was determined. Experimental solubility was correlated by the modified Apelblat equation, the λh model and the NRTL model. The melting point of p -Acetamidobenzoic acid was estimated by the group contribution method. Sigma profiles and solvation free energy were computed on the basis of COSMO-RS model. Abstract: The solubility of p -Acetamidobenzoic acid (PAABA) in 12 pure organic solvents was measured using the gravimetric method in the temperature range of 283.15 K to 323.15 K. It was discovered that the solubility curves in different solvents cross each other when the temperature increased. Besides, the modified Apelblat equation, the λh model and the NRTL model were used to fit the measured solubility data of PAABA and the modified Apelblat equation and λh model gave the minor deviation compared with the NRTL model. The underlying mechanism between PAABA and solvent molecules was revealed in light of physical properties, sigma profiles and solvation free energy analysis, based on COSMO-RS model. The results indicated that the solubility of PAABA in most alcohol solvents are related to the value of solvation free energy. These data are helpful to further study the crystallization process of PAABA.